Comparison of the monocyte-to-HDL cholesterol ratio between patients with STEMI and NSTEMI: A retrospective observational study - Abdullah Algın; Serdar Özdemir (National Scientific Medical Center, 2021)
Introduction This study sought to compare patients with ST-segment elevation myocardial infarction and non-ST-segment elevation myocardial infarction in terms of the monocyte-to-HDL cholesterol ratio. Materials and Methods A total of 79 patients with non-ST-segment elevation myocardial infarction and 30 patients with 30 ST-segment elevation myocardial infarction were included in the study. Demographics, comorbidities, smoking status, medical history, and initial laboratory findings were retrospectively noted from the hospital computer-based patient data system. Results Significant differences were detected between the ST-segment elevation myocardial infarction and non-ST-segment elevation myocardial infarction groups in relation to the neutrophil count [7.27 (6.05-9.05) versus 5.41 (4.26-7.21), p<0.001] and mean platelet volume [9.4 (8.8-10) versus 8.6 (7.3-9.5), p=0.002]. There was no statistically significant difference between the two groups in the term of the monocyte-to-HDL cholesterol ratio [0.016 (0.012-0.021) versus 0.016 (0.011-0.024), p=0.757, Bonferroni-corrected p value: 0.0033)]. Conclusion Based on the results of our study, the monocyte-to-HDL cholesterol ratio did not significantly differ between the patients with ST-segment elevation myocardial infarction and those with non-ST-segment elevation myocardial infarction.